High-pressure phase equilibrium data and coprecipitation of methionine and ethyl cellulose in carbon dioxide + ethanol + acetic acid - Laurintino, Thuany Naiara Silva (2023)
Tese (doutorado) - Universidade Federal de Santa Catarina, Centro Tecnológico, Programa de Pós-Graduação em Engenharia Química, Florianópolis, 2023.